Germany : Report on Observance of Standards and Codes-Fiscal Transparency. (IMF Staff Country Reports; Country Report ;, 2003)
This report provides an assessment of fiscal transparency in Germany. The assessment has two parts. The first is a description of practices, prepared by the IMF staff on the basis of discussions with the authorities, their comprehensive responses to the fiscal transparency questionnaire, and other available information. The second part is an IMF staff commentary on fiscal transparency in Germany. This assessment focuses on the information that the federal government and its agencies provide about the general government.